JENIS DAN FUNGSI TINDAK TUTUR DOSEN DALAM INTERAKSI PEMBELAJARAN BAHASA ARAB DI UIN MALANG - Wahyudi Wahyudi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
This study aims at describing the types and functions of language teachers follow the interaction of learning Arabic I at UIN Malang. Based on theexposure data and fieldwork findings and discussion of the results can bepresented that in the Arabic language learning, teachers use five types ofspeech acts, i.e. acts directive, assertive acts, acts commissive, expressive acts,acts declarative. Directive speech act types occupy a dominant role, andassertive, commissive, expressive, declarative fam. In terms of the function ofspeech acts ilocusive lecturer (Leech), there are social functions and educationalfunctions. Social function consists of four categories: (1) competitive function,(2) convivial function, (3) collaborative function, (4) the function conflictive.Among the four functions conflictive function of at least the data findings.While the educative function of speech acts faculty consists of nine types,namely (1) led to a positive impression of the material, (2) directing the focus,(3) inclusively learning situations, (4) exclusively learning situations, (5)disclose specifics, (6) encourage students to build conclusions (8) controls thelearning situation (9) provide motivation to students. Based on these results itcan be concluded that the speech acts associated with the faculty as well associal issues are also related to the learning objectives